Pengaruh Gaya Kepemimpinan dan Insentif terhadap Motivasi Serta Dampaknya terhadap Kinerja Pegawai Dinas Peternakan dan Perikanan Kabupaten Bungo - M Alhudhori; Evi Adriani; M Zahari MS; Albetris Albetris (Universitas Batanghari Jambi, 2019)
The performance of organization can be seen to the extent of work productivity has been produced. Generally, productivity is defined as the influence between real and physical results with actual input. This study discusses the influence of leadership style and intensive on motivation and its impact on performance in the Bungo District Livestock and Fisheries Office. Data were obtained using questionnaire and literature review methods, with 54 respondents. Then the data were analyzed using descriptive and statistical methods through path analysis. This study resulted in a leadership style, incentives, motivation and performance of the Bungo District Animal Husbandry and Fisheries Office, both for the leadership style with a score of 1930, for incentives with a score of 1438, for motivation with a score of 804 and performance at a score of 2342 in the very high category. Leadership style towards the motivation of the Bungo Regency Animal Husbandry and Fisheries Office has a direct or indirect influence with a value of 20.35%. The incentives for the motivation of the Bungo Regency Animal Husbandry and Fisheries Office have a direct or indirect influence with a value of 0.205%. The leadership style and incentives for the motivation of the Bungo Regency Animal Husbandry and Fisheries Office have a direct or indirect influence with a value of 2.86%. There is an influence of leadership style on the performance of the Bungo Regency Animal Husbandry and Fisheries Office with a value of 1.43%. There is an incentive effect on the performance of the Bungo Regency Animal Husbandry and Fisheries Office with a value of 2.65%. The leadership style and incentives for the performance of the Bungo Regency Animal Husbandry and Fisheries Office have an influence of 2.471%. The influence of motivation on the performance of the Bungo District Animal Husbandry and Fisheries Office is at 4.057%. Leadership styles and incentives through motivation on the performance of the Bungo District Animal Husbandry and Fisheries Office have an effect of 1.478%.